2012
DOI: 10.1016/j.bbrc.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-activated protein kinase in cerebella of Atm−/− mice is attributable to accumulation of reactive oxygen species

Abstract: Ataxia telangiectasia (A-T) is an inherited disease, the most prominent feature of which is ataxia caused by degeneration of cerebellar neurons and synapses. The mechanisms underlying A-T neurodegeneration are still unclear, and many factors are likely to be involved. AMP-activated protein kinase (AMPK) is a sensor of energy balance, and research on its function in neural cells has gained momentum in the last decade. The dual roles of AMPK in neuroprotection and neurodegeneration are complex, and they need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
6
13
0
Order By: Relevance
“…ATM deficiency affects the cerebellum, leading to poor motor coordination in A‐T patients [1, 3, 4]. We have also previously shown that degenerated PCs occur in the Purkinje cell layer (PCL) of the cerebellum of Atm −/− mice [6, 10]. Therefore, we investigated whether the cerebellum exhibits atrophy in Atm −/− mice and whether the protective effect of SB203580 influences cerebellar PCs in Atm −/− mice.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…ATM deficiency affects the cerebellum, leading to poor motor coordination in A‐T patients [1, 3, 4]. We have also previously shown that degenerated PCs occur in the Purkinje cell layer (PCL) of the cerebellum of Atm −/− mice [6, 10]. Therefore, we investigated whether the cerebellum exhibits atrophy in Atm −/− mice and whether the protective effect of SB203580 influences cerebellar PCs in Atm −/− mice.…”
Section: Resultssupporting
confidence: 93%
“…This phenotype is similar to recent observations in the PCs in the cerebellar tissue from an A‐T patient [4]. In addition, Atm‐null mice have movement coordination defects that are consistent with cerebellar dysfunction [1013]. Together, these findings establish that some neuropathological abnormalities seen in A‐T patients are present in Atm −/− mice, indicating that these mice are a useful model by which to study A‐T neurodegeneration.…”
Section: Introductionsupporting
confidence: 87%
“…Notably, inhibiting ATM led to an increase in DNA damage shown by H2AX phosphorylation and tubular cell apoptosis, suggesting that ATM may play a cytoprotective role probably by inducing DNA repair(Ma et al, 2014). In line with this inference, ATM deficiency in brain induced significantly higher ROS (Kuang et al, 2012). In addition, p53 as an important effector of DDR apparently plays important roles in ischemic AKI.…”
Section: Dna Damage Response In Ischemia/reperfusion Kidney Injurysupporting
confidence: 59%
“…While the mechanisms underlying the widespread degenerations in A-T are unclear, an increased oxidative burden seems to be a contributor (Barlow et al 1999;Chen et al 2003;Guo et al 2010;Hayashi et al 2012;Kamsler et al 2001;Kim and Wong 2009;Kuang et al 2012;Ludwig et al 2013;Quick and Dugan 2001;Reichenbach et al 2002;Rotman and Shiloh 1997;Tchirkov and Lansdorp 2003;Yang et al 2014;Ziv et al 2005). It has been suggested that the high oxidative burden could be due to accumulation of reactive oxidant species (ROS) from mitochondrial dysfunction (Ambrose et al 2007;Valentin-Vega et al 2012), a "byproduct" of defective DNA repair (Dar et al 1997) or/and a defect in the cellular antioxidant response (for review, see Ambrose and Gatti 2013).…”
Section: Introductionmentioning
confidence: 99%